Advancements and challenges in personalized neoantigen-based cancer vaccines - Singh, Parminder; Khatib, Mahalaqua Nazli; R, Roopashree; Kaur, Mandeep; Srivastava, Manish; Barwal, Amit; Rajput, G. V. Siva; Rajput, Pranchal; Syed, Rukshar; Sharma, Gajendra; Kumar, Sunil; Shabil, Muhammed; et al. (Oncology Reviews, 2025)
Advancements in personalized neoantigen-based cancer vaccines are ushering in a new era in oncology, targeting unique genetic alterations within tumors to enhance treatment precision and efficacy. Neoantigens, specific to cancer cells and absent in normal tissues, are at the heart of these vaccines, promising to direct the immune system specifically against the tumor, thereby maximizing therapeutic efficacy while minimizing side effects. The identification of neoantigens through genomic and proteomic technologies is central to developing these vaccines, allowing for the precise mapping of a tumor’s mutational landscape. Despite advancements, accurately predicting which neoantigens will elicit strong immune responses remains challenging due to tumor variability and the complexity of immune system interactions. This necessitates further refinement of bioinformatics tools and predictive models. Moreover, the efficacy of these vaccines heavily depends on innovative delivery methods that enhance neoantigen presentation to the immune system. Techniques like encapsulating neoantigens in lipid nanoparticles and using viral vectors are critical for improving vaccine stability and delivery. Additionally, these vaccines contribute towards achieving Sustainable Development Goal 3.8, promoting universal health coverage by advancing access to safe and effective cancer treatments. This review delves into the potential of neoantigen-based vaccines to transform cancer treatment, examining both revolutionary advancements and the ongoing challenges they face.